Lenguage, silence, and exclusion: a critical approach to symbolic bullyng in secondary school (Praxis Educativa, 2026)
The article presents a critical approach to symbolic violence in secondary schools, based on a situated qualitative research project co-authored by a teacher education student and her thesis advisor during the professional practicum process. Through the use of a reflective journal and interviews with teachers, the study identified everyday forms of exclusion that operate through language, silence, humor, and digital technologies. The findings reveal that these symbolic violences are normalized and rarely questioned, both by students and by teachers, whose interventions often focus more on control than on reflection. The article argues that these forms of violence are linked to modern school structures that hierarchize knowledge and silence subjectivities. From a decolonial, feminist, and critical pedagogical perspective, the article defends reflective writing as a tool for epistemic interruption and symbolic resistance. It concludes that schools must be reconfigured as spaces of situated truth, where subaltern voices are heard and embodied knowledge is legitimized. The research proposes the integration of the reflective journal as a pedagogical device in teacher education, to enable the narration of what hurts, discomforts, or remains silenced, thus advancing toward a pedagogy of difference and symbolic restitution.